The Relationship of Spiritual Intelligence with Quality of Service in Hemodialysis Installations - Mariadi, M.; Ibnu, Faisal; Ratnaningsih, Tri; Zamroni, Asroful Hulam (Indonesian Journal of Global Health Research, 2024)
The quality of nursing services for hemodialysis patients is determined by the role and performance of nurses based on spiritual intelligence. Nurses use spiritual intelligence when providing nursing care to hemodialysis patients so that patients feel satisfaction from actions that have an impact on the quality of service. Therefore, this study aims to analyze the relationship between nurses' spiritual intelligence and service satisfaction in the hemodialysis room. This study used a cross-section design with a sample of 35 nurses and 153 hemodialysis patients at RSUD Dr. Soetomo. This research used a total technique for nurses and a simple random sampling technique for patients in hemodialysis installations. Research data was collected through a questionnaire from the spiritual intelligence variable with a valid test of 0.460-0.906 and a reliable test of 0.361 as well as a patient satisfaction questionnaire related to service quality with a valid test of 0.870-0.982 and a reliable test of 0.785. Research data was processed using a logistic regression test with a p-value ≤ 0.05. The results of the logistic regression test show that the p-value is 0.001, so it can be interpreted that H0 is rejected. This shows that there is a relationship between nurses' spiritual intelligence and the quality of hemodialysis services. Spiritual intelligence will create optimal nurse performance in taking action. The performance of nurses in hemodialysis tasks is quite complex with the number of patients being unbalanced with the number of nurses which influences the quality of nursing services.